The influence of entrepreneurial leadership, work ethic, organizational climate, and work motivation on vocational high school teachers’ performance in Badung regency - Diarini, I Gusti Ayu Agung Sinta; Agung, Anak Agung Gede; Yudana, Made; Werang, Basilius Redan (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the direct and indirect effects of entrepreneurial leadership, work ethic, organizational climate, and work motivation on teachers’ performance in vocational high schools in Badung Regency. A quantitative approach using the PLS-SEM method was applied to test the relationships among variables and provide empirical insights into the factors influencing teacher performance. The sample consisted of 290 vocational high school teachers in Badung Regency. The findings indicate that entrepreneurial leadership, work ethic, organizational climate, and work motivation significantly affect teacher performance. This study contributes by integrating entrepreneurial leadership theory into a teacher performance model within the vocational education context and by offering insights into the indirect effects of these variables on performance. The results enrich the literature on factors influencing educational effectiveness, particularly in vocational schools in Indonesia, and provide implications for developing better educational policies.